2023
DOI: 10.1108/yc-04-2023-1728
|View full text |Cite
|
Sign up to set email alerts
|

A mixed study on the “wow” of impulse purchase on Instagram: insights from Gen-Z in a collectivistic environment

Abubakar Sadiq Muhammad,
Ibrahim Adeshola,
Labaran Isiaku

Abstract: Purpose Generation Z (Gen-Z), sometimes known as “digital natives”, represents the first generation to become immersed in digital communication. In a multicultural environment, this study aims to explore which types of factors are most beneficial in connection with Gen-Z’s impulsive purchase behaviour. Design/methodology/approach This study adopts an exploratory sequential mixed-method design, incorporating both qualitative and quantitative approaches. In Study 1, focus group discussions are conducted to add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Menurut (Muhammad, Adeshola, and Isiaku 2023) studi 1 memperkenalkan model stimulus organism respons (SOR) baru yang disesuaikan dengan sosial media Instagram. Faktor-faktor seperti daya tarik estetika, promosi kelangkaan, dan harga diskon merangsang perilaku pembelian impulsif di Gen-Z.…”
Section: Discussionunclassified
“…Menurut (Muhammad, Adeshola, and Isiaku 2023) studi 1 memperkenalkan model stimulus organism respons (SOR) baru yang disesuaikan dengan sosial media Instagram. Faktor-faktor seperti daya tarik estetika, promosi kelangkaan, dan harga diskon merangsang perilaku pembelian impulsif di Gen-Z.…”
Section: Discussionunclassified
“…We believe the SOR framework to be well suited for this research as it is often used in the marketing domain to study consumers’ behavioral responses, such as it happens with the behaviors of social media users (e.g. Muhammad et al , 2024). Moreover, prior studies (e.g.…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
“…The materialistic nature of Generation Z (Flurry and Swimberghe, 2016), sensitivity to trends and lifestyles, and constant desire to appear fashionable motivate this demographic to purchase items that express their individuality (Djafarova and Bowes, 2021). Muhammad et al (2023) found that Generation Z is susceptible to the positive stimuli that fashion products frequently provide; these stimuli are commonly linked to trends and social, environmental, and multicultural concerns (Johnson and Im, 2014;Razzaq et al, 2018;Slater and Demangeot, 2021) elicitation of positive emotions in response to a positive stimulus induces impulsive purchasing (Gupta and Gentry, 2018;Muhammad, Adeshola and Isiaku, 2023). Therefore, Generation Z is a consumer group susceptible to impulsive purchasing (Djafarova and Bowes, 2021;Munsch, 2021;Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%